Perception of the special troops (comandos) soldiers regarding physical fitness, motor control and psychological skills - Monteiro, Carlos; Dias, Gonçalo; Ramos, Susana; Gomes, Ricardo; Gama, José; M. L. Martins, Fernando; Mendes, Rui; Castro, Maria António ([Multidisciplinary Digital Publishing Institute], 2022)
Physical fitness and motor skills are considered important attributes for the military, affecting their professional performance. The high physical and psychological demand that the special forces are subjected to requires the acquisition of a set of volitional skills such as resilience, effort, perseverance, or resistance to frustration, which are worthy of further research. This study aimed to analyse the perception of the special troops (commandos) in physical fitness, motor control and psychological skills. A total of 35 male soldiers that ended the commando recruit training program (21.69 ± 2.36 years old) were investigated. A questionnaire was applied to verify differences in perception of physical fitness, motor capacity, physical effort and military training during recruit training according to age, education, work experience and sports background. Descriptive statistics were used to characterize the participants. All data collected were analysed using IBM-SPSS Statistics, version 24. Our results revealed differences in the importance given to the training of motor skills within military training (χ2 = 19.284; p = 0.023), conditional motor skills – speed (χ2 = 17.378; p = 0.043), coordinative motor skills—motor control (χ2 = 20.616; p = 0.014), psychological skills in a military context (χ2 = 13.730; p = 0.008), volitional skills—resistance to frustration (χ2 = 21.568; p = 0.043) and volitional skills—psychological resistance (χ2 = 29.144; p = 0.004). The participants highlighted the importance of instructors having scientific knowledge in physical education to provide military physical training to be better prepared for this purpose. We concluded that motor skills and psychological abilities tend to be equally important in the context of military training. Physical fitness and motor skill development can be considered essential in military training for most of the inquired participants.
Keywords: commandos; military training; motor skills; psychological skills